Re-circulating rice dryers suitable for large amount of loading capacity. It generally comprises of two parts, the tempering section and a drying section, and the grains are dried in an intermittent way until the final moisture content of the grains can be achieved. Wet grains are initially dried for about 11 minutes within the drying section of the dryer. The grains then are conveyed to the tempering section where it will be stored for about 40 to 50 minutes. At every passes, about less tha - Totok Prasetyo; Kamaruddin Abdullah; Armansyah H. Tambunan; Leopold Nelwan; I Made K.D (Forum Pasca Sarjana, 2009)
Re-circulating rice dryers suitable for large amount of loading capacity.  It generally comprises of two parts, the tempering section and a drying section, and the grains are dried in an intermittent way until the final moisture content of the grains can be achieved.  Wet grains are initially dried for about 11 minutes within the drying section of the dryer.  The grains then are conveyed to the tempering section where it will be stored for about 40 to 50 minutes.  At every passes, about less than 2%(wb) of the moisture content can be removed from the grains. The number of passes required to accomplish a drying process in a recirculation dryer depends on the initial moisture content and the amount of rough rice to be dried.  The drying and tempering duration can be adjusted by means of a mechanical valve.  The purpose of this study was to examine the performance of re-circulating dryers equipped with pneumatic conveyor instead of bucket elevator to reduce electricity cost and heated using a proper blend between kerosene and jatropha oil.  Several experimental runs had been conducted under a constant drying temperature of 60oC and was controlled by adjusting the rate of fuel consumption.  The experimental results showed that the drying efficiency was in the range of 22.2% to 31.1%, the specific energy consumption was between 3.475-4.785 MJ/kg H2O evaporated, fuel consumption at 0.95 to 1.15 (liters/hr) and the drying rate was 0.9%/hr.  The entire drying operation using 465 kg of rough rice required 10 hours of drying time with 74.3% of head yield.  Mathematical model used in this study also had indicated close agreement with experimental data.   Key words: re-circulating dryer, pneumatic conveyor, drying performance, tempering period, bio-kerosene blend